THE SOUTHWESTERN EDGE OF THE NORTH BAIKAL BASIN: GEOLOGIC STRUCTURE AND CORRELATION WITH CENOZOIC SECTIONS OF OL'KHON AND BDP-96 AND BDP-98 CORES - Khlystov O.M.; Mats V.D.; Batist M.De. (My University, 2001)
The paper presents new details of the structure of the basement and sedimentary cover of the southwestern edge of the North Baikal basin. The basement structure involves smaller-scale structures (Maloe More basin, Zama basin, and Zunduk-Zama horst), which, in turn, comprise third-order features. The presence of several en-echelon NE striking sub-basins within the Maloe More and Zama basins indicates that the tectonic framework of the region formed by listric and dextral faulting. Seismostratigraphy data and analysis of uppermost bottom sediments from BDP-96 and BDP-98 cores revealed three seismic layers in the sediment section, which are separated by discontinuities and can be correlated with deposits exposed on land in the neighboring Ol'khon region. Unit A' (X) correlates with the Lower-Middle Oligocene Ular'yar Formation, unit A, with the Lower-Middle Miocene Tagai Formation, and unit B, with the Upper Miocene-Pliocene Sasa Formation and with Quaternary deposits. The upper section of the Maloe More fill includes a separate seismic horizon correlatable with a layer of widely distributed fine-grained sand. Unit B, comprises three deposition centers within the limits of the Maloe More basin, i.e., large lakes existed in the region prior to the final stage of transgression from the North Baikal basin. Thus, the southwestern edge of the Baikal basin has an intricate structure and underwent a complex evolution.
Keywords: Cenozoic; Cenozoic; Кайнозой